Pengaruh Penggunaan Lagu Anak-Anak Terhadap Peningkatan Kosakata Bahasa Inggris Siswa Kelas 1 SD - Dinda Aliyah Putri; Febby Willya Yolanda; Herani Citra; Putri Eka Nur Rahmadona (Universitas Palangka Raya, 2024)
This study aims to evaluate the effectiveness of the use of children's songs in increasing English vocabulary for grade 1 elementary school students. With the classroom action research method (PTK), this study was conducted in three cycles which included the planning, implementation, observation, and reflection phase. The research subjects were 13 students in grade 1 in SD Negeri 067097, Medan Barat District, Medan City. Data is collected through observation and documentation studies. The results showed that the use of children's songs in learning English had a positive impact on increasing student vocabulary. The percentage of learning completeness increased significantly from pre-cycle (33.33%), cycle I (53.84%), to cycle II (69.22%). In addition, this method also increases student motivation and interest in learning, providing a fun learning alternative, and helping teachers in improving the quality of teaching. This study contributed a positive to the practice of teaching English at the basic level by utilizing media close to the world of children, such as songs.